Alternative lengthening of telomeres in childhood neuroblastoma from genome to proteome - Stainczyk, Sabine; Sieverling, Lina; Nadler-Holly, Michal; Ziehm, Matthias; Toprak, Umut H.; Herrmann, Carl; Ishaque, Naveed; Okonechnikov, Konstantin; Gartlgruber, Moritz; Park, Young-Gyu; Wecht, Elisa Maria; Savelyeva, Larissa; et al. (Nature Communications, 2021)
Telomere maintenance by telomerase activation or alternative lengthening of telomeres (ALT) is a major determinant of poor outcome in neuroblastoma. Here, we screen for ALT in primary and relapsed neuroblastomas (n = 760) and characterize its features using multi-omics profiling.
Gesehen am 26.02.2021